2016
DOI: 10.1093/heapol/czw007
|View full text |Cite
|
Sign up to set email alerts
|

Performance of retail pharmacies in low- and middle-income Asian settings: a systematic review

Abstract: In low- and middle-income countries (LMIC) in Asia, pharmacies are often patients’ first point of contact with the health care system and their preferred channel for purchasing medicines. Unfortunately, pharmacy practice in these settings has been characterized by deficient knowledge and inappropriate treatment. This paper systematically reviews both the performance of all types of pharmacies and drug stores across Asia’s LMIC, and the determinants of poor practice, in order to reflect on how this could best b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
215
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(226 citation statements)
references
References 81 publications
(326 reference statements)
7
215
0
4
Order By: Relevance
“…However, a review of pharmacy practice in Asia reported similar management for various presentations of childhood diarrhoea going back 30 years, that is, before the advent of chains, indicating that major changes in the behaviour of independents do not appear to have occurred in recent times. 3 The main difference between pharmacy types observed was the lower use by chains of harmful POMs for the patient with diarrhoea. There is evidence that some of these POMs, such as antibiotics, are high profit generators.…”
Section: Bmj Global Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a review of pharmacy practice in Asia reported similar management for various presentations of childhood diarrhoea going back 30 years, that is, before the advent of chains, indicating that major changes in the behaviour of independents do not appear to have occurred in recent times. 3 The main difference between pharmacy types observed was the lower use by chains of harmful POMs for the patient with diarrhoea. There is evidence that some of these POMs, such as antibiotics, are high profit generators.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…[1][2][3] All too often, medicine use in these settings is 'irrational'. That is, patients do not receive the appropriate medicines, in doses that meet their individual requirements, for an adequate duration, and at the lowest cost.…”
Section: Bmj Global Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…antibiotics for the treatment of the symptoms of a common cold or influenza, or appropriate drugs in suboptimal doses. 24 Suboptimal doses may be all that the patient can afford. In Peru and central Thailand, private retail pharmacies, where dispensing could not be guided by the antibiotic-resistance profiles of the causative agents, were found to be the most common source of antibiotics for the treatment of sexually transmitted diseases.…”
Section: Supply Problemsmentioning
confidence: 99%
“…These retail drug shops are often the first point of contact with the health care system and preferred channel for purchasing medicines for the majority of people (Miller & Goodman, 2016). Bangladesh is no exception to this.…”
Section: Introductionmentioning
confidence: 99%